Improving Cultural Analysis - Lizardo, Omar (American Sociological Review, 2017)
While influential across a wide variety of subfields, cultural analysis in sociology continues to be hampered by coarse-grained conceptualizations of the different modes in which culture becomes personal, as well as the process via which persons acquire and use different forms of culture. In this article, I argue that persons acquire and use culture in two analytically and empirically distinct forms, which I label declarative and nondeclarative. The mode of cultural acquisition depends on the dynamics of exposure and encoding, and modulates the process of cultural accessibility, activation, and use. Cultural knowledge about one domain may be redundantly represented in both declarative and nondeclarative forms, each linked via analytically separable pathways to corresponding public cultural forms and ultimately to substantive outcomes. I outline how the new theoretical vocabulary, theoretical model, and analytic distinctions that I propose can be used to resolve contradictions and improve our understanding of outstanding substantive issues in empirically oriented subfields that have recently incorporated cultural processes as a core explanatory resource.